Endline Report for the Self-Supporting Rural Development Project with Saemaul Undong's Participatory Approach in Myanmar - Kim, Booyuel; Choi, Syngjoo (KDI School of Public Policy and Management, 2020)
The Self-Supporting Rural Development Project with Saemaul Undong's Participatory Approach (hereafter SMU) in Myanmar, implemented jointly by Korea International Cooperation Agency (KOICA) and the Ministry of Agriculture, Livestock, and Irrigation (MOALI) from 2014 to 2019, is the largest rural development project in Southeast Asia implemented by KOICA. Excluding the budget for the construction of the Saemaul Undong Training Institute in Myanmar, the project is worth more than 10 billion Korean won (equivalent to USD 9 million), which includes the budget for the implementation of rural community development projects in 100 pilot villages across nine regions in Myanmar over three years. As the scale of KOICA's development projects has expanded dramatically, and projects with large budgets of over 10 billion won, including Myanmar's rural community development projects, have increased significantly, there have been increasing discussions on how to evaluate various projects implemented by KOICA. The evaluation method used by KOICA can be described as Process Evaluation using Project Design Matrix(PDM), which summarizes the logical framework based on the Theory of Change. While the PDM evaluated in the order of inputs, activities, outputs, outcomes, and impacts has the advantage of being particularly useful for process evaluation, it assumes a causal relationship between inputs/activities and outcomes/impacts and thus cannot be scientifically proven. In an effort to address these limitations of process evaluation, impact evaluation method focused on identifying causal relationships has received increasing attention. Abhijit Banerjee (University of MIT), Esther Duflo (University of MIT), and Michael Kremer (University of Harvard) have conducted impact evaluations applying a randomized controlled trial (RCT) to various development projects since the mid-1990s. They have also received the 2019 Nobel Prize in Economics for their contributions to poverty alleviation and development policies based on scientific evidence derived from impact evaluation findings. National aid agencies such as USAID and DFID, and inter-governmental organizations such as the World Bank and the Asian Development Bank have been actively conducting impact evaluations of their development projects. In particular, the World Bank has established the Development Impact Evaluation Initiative (DIME) in order to evaluate their major projects. KOICA also carried out an impact evaluation, along with process evaluation, when implementing the Myanmar rural community development project in line with these international evaluation trends.